De la clandestinité à l'affirmation : pour une histoire de la communauté gaie montréalaise - Higgins, Ross (Comeau & Nadeau, 1999)
Survol historique de la communauté gaie-lesbienne de Montréal. D'après l'auteur, ce premier volume sera suivi d'une publication ultérieure où son enquête sera présentée de façon plus globale.
Section: 165, [2] p
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire; histoire et politique; hétérosexisme; identités LGBTQIA2+; justice sociale; militance; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; shm4000; soc2014; systèmes d'oppressions; thématiques

The good-natured feminist: Ecofeminism and the quest for democracy - Sandilands, Catriona (University of Minnesota Press, 1999)
The Good-Natured Feminist inaugure une conversation soutenue entre l'écoféminisme et les écrits récents du postmodernisme féministe et de la démocratie radicale. Partant de l'hypothèse que l'écoféminisme est un corpus de théorie démocratique, le livre raconte comment le mouvement est né des débats sur la « nature » ​​dans les féminismes radicaux nord-américains, comment il s'est ensuite mêlé à la politique identitaire et comment il cherche maintenant à inclure la nature dans la conversation démocratique et, surtout, de politiser les relations entre genre et nature dans les milieux tant théoriques qu'activistes.
http://site.ebrary.com/id/10151040
Keywords: amériques; approches et analyses; cours; environnement; fem3600; genre; identités LGBTQIA2+; militance; postmodernisme; premier cycle; ressource en ligne; régions géographiques; thématiques; écoféminisme; états-unis

Strange sisters the art of lesbian pulp fiction, 1949-1969 - Zimet, Jaye (Viking Studio, 1999)
A vivid, sexy, and titillating journey into the steamy underworld of the dime novel. In the scandalous world of pulp fiction in the 1950s and into the 60s, detectives, gangsters, and mad doctors were joined on the racks by bad girls, dissolute youths, drug-crazed beatniks, and other assorted miscreants and misfits. Where romance met with soft porn there was also a surprisingly large population of butch brunettes pursuing and seducing blond femmes. This was an alternate universe of erotic pulp fiction where gals and dolls were exploring the illicit pleasures of lesbian love–much to the delight of a largely male, heterosexual readership. Before the sexual revolution of the 1960s, these books offered a thrilling peek into the deviant underworld of wild passion and scandalous sex. Strange Sisters is a collection of the cover art of these wildly wicked novels. The women who writhe across the covers of books such as Strange Lust ("She Wanted a Woman–Then She Met Another Woman Obsessed by the Same Burning Hunger") and Women's Barracks ("The Frank Autobiography of a French Girl Soldier") sizzle with sexual energy and freedom–in a high-camp defiance of the prudish, conservative 1950s. Bold, kitschy-colorful, and fraught with sexual tension, the covers of Strange Sisters are a siren call to the retro-groovin' man, or woman, in your life.
Keywords: 1900-1999; 1950-1959; 1960-1969; amériques; corps; fiction; identités LGBTQIA2+; personnes lesbiennes; périodes historiques; régions géographiques; sexualité; thématiques; états-unis